Analysis of two‐stage waste heat recovery based on natural gas‐fired boiler. (12th September 2019) - Cui, Xinying; Zhang, Haiyan; Guo, Jiangfeng; Huai, Xiulan; Xu, Min
Summary: Waste heat recovery (WHR) is crucial to the efficiency improvement of natural gas‐fired boiler systems. Two‐stage WHR systems based on the natural gas‐fired boiler were analyzed from the viewpoints of thermal efficiency and heat transfer irreversibility. An overall entransy dissipation‐based thermal resistance was derived to evaluate the irreversibility of WHR, including the entransy dissipations during condensation and in absorption heat pump (AHP). Compared with the basic WHR system, the two‐stage WHR systems have higher boiler efficiency and less irreversibility. The air‐humidified system recycles both the heat and vapor in flue gas, while the unutilized latent heat in the recovered vapor causes the boiler to be less efficient than the AHP system. Investigation on heat exchanger effectiveness of two‐stage WHR systems illustrated: in the two‐stage WHR system with air humidification, the increasing effectiveness of both heat exchangers could effectively increase boiler efficiency and reduce heat transfer irreversibility. In the two‐stage WHR system with AHP, boiler efficiency has a local optimum when the dew point occurs near the outlet of the first heat exchanger; increasing the second heat exchanger effectiveness is more efficient in improving boiler efficiency. The present work may provide available references and guidance for the design and optimization of the two‐stage WHR systems. Abstract : Two‐stage waste heat recovery (WHR) systems(air‐humidified or absorption heat pump (AHP) system) based on natural gas‐firedboiler were analyzed from the viewpoints of thermal efficiency and entransydissipation innovatively. An overall entransy dissipation‐based thermalresistance was derived to evaluate the heat transfer irreversibility of WHR, including the entransy dissipations of condensation and AHP. Effect of two heatexchanger effectiveness on WHR was analyzed to fill the gap of two‐stage heattransfer, which provides guidance for the design and optimization.